Climate change impacts of e-fuels for aviation in Europe under present-day conditions and future policy scenarios. (15th April 2023) - Ballal, Vedant; Cavalett, Otávio; Cherubini, Francesco; Watanabe, Marcos Djun Barbosa
Graphical abstract: Highlights: Climate impacts of e-fuels can vary, depending on the source of electricity, CO2  and H2, and their production technologies. Today, e-fuels have smaller climate impacts than fossil fuels only if produced with a clean electricity source. By 2050, stricter climate policies can decarbonize average European electric grid and cut climate impacts of e-fuels by 84%. Climate change impacts of future e-fuels can be up to 58% lower than those of fossil fuels. A clean electricity for H2  production and the use of non-fossil CO2  are key determinants of the climate benefits of e-fuels. Abstract: 'E-fuels' or 'synthetic fuels' are hydrocarbon fuels synthesized from hydrogen (H2 ) and carbon dioxide (CO2 ), where H2 can be produced via electrolysis of water or steam reforming of natural gas, and CO2 is captured from the combustion of a fossil or biogenic source or directly from the atmosphere. E-fuels are drop-in substitutes for fossil fuels, but their climate change mitigation benefits are largely unclear. This study evaluates the climate change impacts of e-fuels for aviation by combining different sources of CO2 and H2 up to 2050 under two contrasting policy scenarios. The analysis includes different climate metrics and the effects of near-term climate forcers, which are particularly relevant for the aviation sector. Results are produced for European average conditions and for Poland and Norway, two countries with high and low emission intensity from their electricity production mix. E-fuels can either have higher or lower climate change impacts than fossil fuels, depending on multiple factors such as, in order of importance, the electricity mix, the origin of CO2, the technology for H2 production, and the electrolyzer efficiency. The climate benefits are generally higher for e-fuels produced from CO2 of biogenic origin, while e-fuels produced from CO2 from direct air capture or fossil fuel combustion require countries with clean electricity to outperform fossil fuels. Synthetic fuels produced from H2 derived from natural gas have higher impacts than fossil fuels even when coupled with carbon capture and storage, if CO2 is sourced from fossil fuels or the atmosphere. Climate change impacts of e-fuels improve in the future, and they can all achieve considerable climate change mitigation in 2050 relative to fossil jet fuel, provided that strict climate policy measures are implemented to decarbonize the electricity sector. Under reduced policy efforts, future climate impacts in 2050 of e-fuels from atmospheric or fossil CO2 are still higher than those of fossil jet fuels with an average European electricity mix. This study shows the conditions to maximize the climate change mitigation benefits of e-fuels, which essentially depend on progressive decarbonization of the electricity sector and on reduced use of CO2 sourced from fossil fuels.